Cardiac Myosin Activation for the Treatment of Systolic Heart Failure - Bernier, Thomas D. (J Cardiovasc Pharmacol, 2021)
Left ventricular systolic dysfunction is the hallmark pathology in heart failure with reduced ejection fraction. Increasing left ventricular contractility with beta-adrenergic receptor agonists, phosphodiesterase-3 inhibitors, or levosimendan has failed to improve clinical outcomes and, in some situations, increased the risk of sudden cardiac death. Beta-adrenergic receptor agonists and phosphodiesterase-3 inhibitors retain an important role in advanced heart failure. Thus, there remains an unmet need for safe and effective therapies to improve left ventricular systolic function. Two novel cardiac myotropes, omecamtiv mecarbil and danicamtiv, target cardiac myosin to increase left ventricular systolic performance. Neither omecamtiv mecarbil nor danicamtiv affects cardiomyocyte calcium handling, the proposed mechanism underlying the life-threatening arrhythmias associated with cardiac calcitropes and calcium sensitizers. Phase 2 clinical trials have demonstrated that these cardiac myosin activators prolong left ventricular systolic ejection time and promote left ventricular and atrial reverse remodeling. At higher plasma concentrations, these agents may be associated with myocardial ischemia and impaired diastolic function. An ongoing phase 3 clinical trial will estimate the clinical efficacy and safety of omecamtiv mecarbil. Additional study of these agents, which have minimal hemodynamic and renal effects, is warranted in patients with advanced heart failure refractory to guideline-directed neurohormonal blockers.